The role of StAR-D3 in HER2 overexpressing breast cancer - Mele, T (2012)
Background: HER2 overexpression in breast cancer is associated with poor prognosis. Trastuzumab is an anti-HER2 therapy and its clinical benefits have been established both in metastatic and early disease. However, Trastuzumab resistance is a common problem, even for patients who initially respond to the treatment. StAR-D3 gene is localized on the 17q12 amplicon and it is co-amplified with HER2. The contribution of StAR-D3 in HER2 positive breast cancer and its effect on Trastuzumab treatment and resistance has not been fully investigated. Materials and Methods: StAR-D3 expression was analyzed by qRT-PCR and western blot in HER2 over-expressing breast cancer cell lines (BT474 and SKBR3) compared to MCF7. BT474 and MCF7 cells were transfected with specific si-RNA targeting StAR-D3 and the effect on cell viability was observed. In BT474, StAR-D3 knockdown was combined with Trastuzumab treatment and cell viability, together with protein expression of HER2 downstream effectors, were assessed. In BT474, the influence of StAR-D3 knockdown on apoptosis was assessed by FACS analysis. StAR-D3 gene expression analysis was carried out, using aCGH analysis, in a subset of 198 breast cancer patients. To optimize IHC staining procedure for clinical samples, BT474 cell pellet was stained with anti-StAR-D3 antibodies. Results: Together with HER2, StAR-D3 was highly expressed in SKBR3 and BT474, compared to MCF7 cells. In BT474 cells, StAR-D3 knockdown significantly decreased cell viability; this effect was partially due to increased apoptosis. The combination of StAR-D3 knockdown and Trastuzumab was additive in the decrease of pAKT level and cell viability, compared to either condition alone. Furthermore, StAR-D3 knockdown seemed to reverse Trastuzumab resistance in these cells. Gene expression analysis confirmed the co-expression of HER2 and StAR-D3. Unfortunately, immunocytochemistry on cell pellet was not conclusive. Conclusions: These data suggest that StAR-D3 plays an important role in the mainteinance of cell survival as well as Trastuzumab resistance in HER2 positive breast cancer cells; further analyses on the functional role of StAR-D3 can add useful insights to breast cancer treatment.